Integrating DNA barcoding, bioclimatic modelling, and habitat analysis to assess the diet and potential spread of Vespula germanica (Fabricius, 1793) in the Western Cape of South Africa - Molepo, Dikobe Karen (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhDConsEcol)--Stellenbosch University, 2026.